Haptoglobin, hemopexin, and related defense pathways—basic science, clinical perspectives, and drug development - Schaer, Dominik J.; Vinchi, Francesca; Ingoglia, Giada; Tolosano, Emanuela; Buehler, Paul W. (Frontiers in Physiology, 2014)
Hemolysis, which occurs in many disease states, can trigger a diverse pathophysiologic cascade that is related to the specific biochemical activities of free Hb and its porphyrin component heme. Normal erythropoiesis and concomitant removal of senescent red blood cells (RBC) from the circulation occurs at rates of approximately 2x106 RBCs/second. Within this physiologic range of RBC turnover, a small fraction of hemoglobin (Hb) is released into plasma as free extracellular Hb. In humans, there is an efficient multicomponent system of Hb sequestration, oxidative neutralization and clearance. Haptoglobin (Hp) is the primary Hb-binding protein in human plasma, which attenuates the adverse biochemical and physiologic effects of extracellular Hb. The cellular receptor target of Hp is the monocyte/macrophage scavenger receptor, CD163. Following Hb-Hp binding to CD163, cellular internalization of the complex leads to globin and heme metabolism, which is followed by adaptive changes in antioxidant and iron metabolism pathways and macrophage phenotype polarization. When Hb is released from RBCs within the physiologic range of Hp, the potential deleterious effects of Hb are prevented. However, during hyper-hemolytic conditions or with chronic hemolysis, Hp is depleted and Hb readily distributes to tissues where it might be exposed to oxidative conditions. In such conditions, heme can be released from ferric Hb. The free heme can then accelerate tissue damage by promoting peroxidative reactions and activation of inflammatory cascades. Hemopexin (Hx) is another plasma glycoprotein able to bind heme with high affinity. Hx sequesters heme in an inert, non-toxic form and transports it to the liver for catabolism and excretion. In the present review we discuss the components of physiologic Hb/heme detoxification and their potential therapeutic application in a wide range of hemolytic conditions.